Characterization of the PP1 interactome from human testis - Fardilha, Margarida Sâncio da Cruz (2011)
Protein phosphorylation is a major regulatory mechanism notably of signal transduction cascades in eukaryotic cells. Protein phosphorylation is catalysed by protein kinases and can be reversed by the action of protein phosphatases. Although phosphatases were discovered more than sixty years ago, their importance as central players in multiple cellular mechanisms was only recently recognized. PP1, a Serine/Threonine specific phosphatase, is involved in important cellular mechanisms such as the cell cycle, muscle contraction and apoptosis, among others. Its role in such diverse cellular processes depends on its interactions with targeting/regulatory subunits. To date, more than 50 regulatory subunits have been identified that bind the catalytic subunit of PP1 determining its function in a specific cellular location. Several isoforms of PP1 are known, termed PP1 , PP1 and PP1 . The gamma isoform undergoes alternative splicing to yield a ubiquitously expressed PP1 1 and a testis-specific PP1 2 isoform. Incubation of non-motile immature sperm with phosphatase inhibitors induces sperm motility, and PP1 2 was implicated in this process. This led us to search for PP1 2-specific interactors in human sperm that could be targeted for infertility therapeutics or in male contraception. To achieve this goal the Yeast Two Hybrid system was used to screen a human testis library for new PP1 binding proteins using both PP1 1 (YTH1) and PP1 2 (YTH2) as baits. We recovered 120 positive clones in YTH1 and 155 positive clones in YTH2. Among these were clones encoding “bona fide” PP1 interactors such as Nek2 and NIPP1, and also previously uncharacterized proteins. We undertook a more detailed study of a novel gene encoding a novel protein that we termed SEARP-T. This protein of 93KDa is expressed mainly in testis and fluorescence immunocytochemistry was used to determine its intra sperm localization. Both PP1 2 and SEARP-T proteins are present in the tail and in the equatorial segment of the head.These results provide new insights into PP1 function in human testis and sperm motility, and indicates that the Yeast Two Hybrid System provides a mean to understand the roles PP1 plays in diverse cellular regulatory events.